Republic of Tajikistan : Third Review of the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Tajikistan's Third Review of the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF), and Request for Waiver of Performance Criterion. Performance under the PRGF has been generally satisfactory. All quantitative performance criteria, two of the three structural performance criteria, and two of the three structural benchmarks were met through end-May 2004. The continuous structural performance criterion prohibiting directed credit by the National Bank of Tajikistan was not observed in May 2004, but this credit was repaid/reversed by late June, and a waiver is requested on this basis.